Production and Characterization of β-glucosidase Obtained by the Solid-State Cultivation of the Thermophilic Fungus Thermomucor indicae-seudaticae N31 - de Cassia Pereira, Josiani [UNESP]; Leite, Rodrigo Simões Ribeiro; do Prado, Heloiza Ferreira Alves [UNESP]; Bocchini Martins, Daniela Alonso [UNESP]; Gomes, Eleni [UNESP]; da Silva, Roberto [UNESP] (Springer Nature, 2015)
In this paper, several agro-industrial wastes (soybean meal and wheat straw, rice and peanut husks, corn cob and corn stover, and sugarcane bagasse) were tested for the production of β-glucosidase by the cultivation of thermophilic fungus Thermomucor indicae-seudaticae N31 in solid-state fermentation (SSF). Among the tested substrates, the highest yields were obtained in soybean meal. Other fermentation parameters were also evaluated, such as initial pH, merge substrates, and fermentation time, as well as the physicochemical characterization of the enzyme. The best results were obtained after 192 h of fermentation with the initial pH adjusted to 6.0. The substrate mixture did not improve the enzyme production by microorganism. The β-glucosidase showed best catalytic activity at pH 4.5 and at 75 °C and remained stable in the pH range from 4.5 to 9.5 and the temperature range 40–75 °C. The enzyme showed 80 % of its activity at a concentration of 15 mM glucose and remained stable up to 20 % ethanol.
Keywords: Solid-state fermentation; Thermomucor indicae-seudaticae N31; β-glucosidase